1970
DOI: 10.1021/ic50088a059
|View full text |Cite
|
Sign up to set email alerts
|

Complexes with sulfur and selenium donors. I. Tris(O,O'-dialkyldithiophosphato)-chromium(III) compounds

Abstract: kZ//kl limits k-CH30H,/k-H2" to a maxiinum value of 1.3 from eq 7. This in turn limits the second term to a value less than 0.1. The data for the chloride system for kJk1 with the value of 1.5 equal to k-cH3oH/k-H2o limit the second term to a value of 2.0. The value of k ' + x -/ k + xis the only variable at constant solvent composition in the second term of eq 7 when k+HzO. U H~O -k k+CHaoHUCH30H > k + x -/ X -] and k'+HzO. ~~2 0 ( 5 ) P. S. Skell, J. H .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The compound was found to be diamagnetic and its formulation as the compound Hg32+(AsF6~)2 was fully confirmed by the Xray crystallographic study which was subsequently carried out and which is reported in this paper. If the yellow solution is treated with a further quantity of AsFs, it becomes colorless and a white crystalline solid is obtained on removal (7) "International Tables for X-Ray Crystallography," Kynoch Press, Birmingham, England, 1962.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compound was found to be diamagnetic and its formulation as the compound Hg32+(AsF6~)2 was fully confirmed by the Xray crystallographic study which was subsequently carried out and which is reported in this paper. If the yellow solution is treated with a further quantity of AsFs, it becomes colorless and a white crystalline solid is obtained on removal (7) "International Tables for X-Ray Crystallography," Kynoch Press, Birmingham, England, 1962.…”
Section: Resultsmentioning
confidence: 99%
“…169 ( 8) 806 ( 6) 216 ( 4) 98 (13) F( 2) 316 (7) 722 ( 5) 34 (3) 78 (10) F( 3) 55 ( 15) 551 ( 10) 146 ( 7) 171 (28) F( 4) 306 ( 10) 575 ( 7) 311 ( 4) 115 ( 16) F( 5) 556 ( 9) 696 ( 6) 203 ( 4) 98 ( 13) F (6) 412 ( 9) 474 ( 6) 114 ( 4 of volatiles. The weight of the solid corresponded to the formation of mercury(I) hexafluoroarsenate, Hg2(AsF6)2, according to the equation 2Hg + 3AsFs -> Hg2(AsF6)2 + AsF3, and the elemental analysis of the compound was in good agreement with this formula.…”
Section: Resultsmentioning
confidence: 99%
“…The 0,0'-dialkyl dithiophosphate complexes Cr [(RO)2PS2]3 (particularly the ethoxy derivative) have been known for some time7,8 and now an extensive series of alkoxy homologs has been investigated. 8 While this paper was in preparation, the synthesis of the Cr(S2PF2)3 complex from F2P(S)SH and chromium metal was also reported;9 however, spectral9,10 and magnetic properties9,10 were only reported in summary. The synthesis of the complex Cr [S2P(CeH3)2]3 from chromium trichloride and the phenyl acid (CelTh-PS2H11,12 and the synthesis and a dipole moment study of Cr[S2P(C2H5)2V3 have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…14 . The ligands behaves as mononegative bidentate and the formula of complexes may be proposed to be [ML X 4 ] (M = Nb/ Ta; LH = 2-aminothiophenol or 2-aminophenol; X = Cl/NCS).…”
Section: Preparation Of Tantalum(v) Complexesmentioning
confidence: 99%